A home for all Jews: citizenship, rights, and national identity in the new Israeli state - Rozin, Orit (The Schusterman series in Israel studies, 2016)
Introduction: Creating citizenship in the new State -- 1. The right to childhood and the age of marriage law -- 2. The right to travel abroad -- 3. Craving recognition